2006
DOI: 10.1590/s0100-40422006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da eficiência do processo de ozonização e ozonização catalítica (Mn II e Cu II) na degradação de fenol

Abstract: Recebido em 3/9/04; aceito em 25/4/05; publicado na web em 10/8/05 COMPARISON OF THE EFFICIENCY OF OZONATION AND CATALYTIC OZONATION (Mn II AND Cu II) IN PHENOL DEGRADATION. This paper discusses the results obtained with homogeneous catalytic ozonation [Mn (II) and Cu (II)] in phenol degradation. The reduction of total phenols and total organic carbon (TOC) and the ozone consumption were evaluated. The efficiency in phenol degradation (total phenol removal) at pH 3, with the catalytic process (Mn (II)), increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…Addition of the catalyst (Mn 2+ ) showed no significant effect on the removal of COD from the wastewater. Some authors (ASSALIN et al, 2006;MAHMOUD;FREIRE, 2007) observed improved removal efficiency of the organic load from wastewater when the catalyst Mn 2+ was added to the ozonation process, at concentrations exceeding 1 mg L -1 . Therefore, the non-significance of Mn 2+ addition may be explained by the low concentrations ([Mn 2+ ] < 0.04 mg L -1 ) used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of the catalyst (Mn 2+ ) showed no significant effect on the removal of COD from the wastewater. Some authors (ASSALIN et al, 2006;MAHMOUD;FREIRE, 2007) observed improved removal efficiency of the organic load from wastewater when the catalyst Mn 2+ was added to the ozonation process, at concentrations exceeding 1 mg L -1 . Therefore, the non-significance of Mn 2+ addition may be explained by the low concentrations ([Mn 2+ ] < 0.04 mg L -1 ) used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…O3 ( The variation ranges between the lower limit and the top of each independent variable were assumed based on literature (Assalin et al, 2006;Mahmoud and Freire, 2007) and preliminary tests.…”
Section: Variables Unitsmentioning
confidence: 99%
“…O processo oxidativo via ozônio tem sido amplamente utilizado no tratamento de efluentes domésticos (SILVA, 2008;SOARES, 2007;SALLA, 2006, entre outros) e industriais (KERN, 2012;KRAUSE, 2009;SOUZA, 2009;ASSALIN et al, 2006;SILVA, 2006). Contudo, não há na literatura estudos da utilização de ozônio no pós-tratamento de efluente advindo da atividade automotiva.…”
Section: Introductionunclassified